Eco-Friendliness and Cost-Effectiveness of Reusable Sanitary Pads for Rural Women: A Model for Menstrual Hygiene Management in Low Resource Settings (Bangladesh Journal of Medical Science, 2024)
Background Menstrual Hygiene Management (MHM) is fundamental to women’s health, well-being, and gender equality. The study aimed to assess the cost-effectiveness and acceptability of reusable sanitary pads among rural women in Pakistan, proposing a scalable model for improving MHM practices in low-income countries. Methods A cross-sectional study was conducted using Multi- Stage Cluster sampling to accomplish a sample size of 340 childbearing-age women from the rural areas of Sindh, Pakistan. The data was collected using a standard questionnaire regarding the affordability and accessibility of reusable versus disposable sanitary pads; further information was also gathered from Market surveys for MHM products. The biodegradability of the pads was assessed using a soil burial test. The data was analyzed using SPSS version 27. Results Our research found a significant preference for reusable sanitary pads. The biodegradability tests demonstrated that reusable pads had a superior degradation rate (1.88%) to disposable pads (1.59%) over four months. Economic assessments showed a low utilization of commercial pads (12.5%) due to affordability issues, with 87.5% using reusable cloths. Despite 70% awareness of menstrual hygiene, 48% of women showed interest in creating sanitary solutions, underscoring the feasibility of implementing locally sourced, cost-effective products across similar socio-economic landscapes. Conclusion The present study underscores the universal applicability of affordable, sustainable MHM solutions in rural communities of low-income countries, advocating for broader implementation of such models to address global menstrual hygiene challenges.Bangladesh Journal of Medical Science Vol. 23 No. 04 October’24 Page : 1030-1037